The Effect of Local Anesthetic Agent Infiltration Around Nephrostomy Tract On Postoperative Pain Control After Percutaneous Nephrolithotomy: A single-centre, randomised, double-blind, placebocontrolled clinical trial - Dundar, Gokce; Gokcen, Kaan; Gokce, Gokhan; Gultekin, Emin Yener (Urology Journal, 2018)
Purpose: Insufficient alleviation of pain after percutaneous nephrolithotomy causes patient dissatisfaction and generates additional morbidity factors by preventing early mobilization. This study investigated the effects of bupivacaine infiltration with two different doses around the nephrostomy tract after percutaneous nephrolithotomy. Materials and Methods: Patients who underwent subcostal single entrance percutaneous nephrolithotomy were randomly divided into 3 groups of 20 patients. While the first and second group were planned to receive bupivacaine at rates of 0.5% and 0.25% respectively, the third group was planned to receive a placebo agent to preserve the doubly blinded nature of the study. Results: A statistically significant difference was found in the number of patients using tramadole. The frequency of analgesic administration was found lower in the two groups that received bupivacaine in comparison to the group that did not, while the time of the first analgesic administration in the group that received high dose bupivacaine was significantly later than the other groups. Although there was no difference between the groups in terms of total amount of analgesic usage, patients who received higher concentrations of bupivacaine were likely to require a lower amount of narcotic agent. The frequency of analgesic administration decreased significantly in patients of both groups that received bupivacaine. Moreover, by administering bupivacaine at a 0.5% rate, fewer patients (50%) required narcotic analgesia and the first time of analgesic administration was found to be significantly later. Conclusion: Administering bupivacaine at a 0.5% rate around the nephrostomy tract after surgery was demonstrated to be more effective.?